2018
DOI: 10.5505/yeditepe.2018.25743
|View full text |Cite
|
Sign up to set email alerts
|

Clinical follow- up of occlusal vertical dimension increase in stainless steel crowns applied with hall technique: A pilot study

Abstract: ÖZET Amaç: Hall teknik (HT) süt azı dişlerinde preparasyon yapıl-madan ve çürük uzaklaştırılmadan paslanmaz çelik kuron (PÇK) simantasyonuyla uygulanabilen minimal girişimsel bir diş tedavi yöntemidir. Preparasyon yapılmadan PÇK'nın simantasyonu sonucu HT oklüzal dikey boyutu arttırmaktadır. Çalışmamızın amacı HT uygulaması ile restorasyon sonrası dikey boyut artışının, tedaviden öncesiyle, hemen tedaviden sonra, 15. ve 30. gününde karşılaştırılmasıdır. Gereç ve Yöntem: Çalışmaya çapraz kapanışı ve parafonksiy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The balanced occlusion usually has been re-established within a few weeks (14,35). Supporting these results, Van der Zee et al (21) and Kaya et al (36) reported that occlusal vertical dimensions were spontaneously corrected after almost one month following the cementation of PMC. Children may tolerate occlusal changes more than adults.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The balanced occlusion usually has been re-established within a few weeks (14,35). Supporting these results, Van der Zee et al (21) and Kaya et al (36) reported that occlusal vertical dimensions were spontaneously corrected after almost one month following the cementation of PMC. Children may tolerate occlusal changes more than adults.…”
Section: Discussionmentioning
confidence: 76%
“…Some studies have shown that the Hall Technique has a negligible effect on the temporomandibular joint, masseter muscle activity, and occlusal vertical dimensions (21,(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%